A new digital 4πγ system with a NaI well-type detector at LMR-CNEA. (April 2018) - Rossi, M.; Balpardo, C.; Arenillas, P.; Cerutti, G.; Ferrari, M.C.
Abstract: A 4πγ integral counting system with a NaI(Tl) well-type detector and a digital interface to acquire measurement data was implemented at LMR-CNEA. The detection efficiency as a function of the energy was computed by Monte Carlo simulations and the total efficiencies for ampoules and point sources were calculated considering all the decay branches. A computer code was developed to analyse data. This program reads the files generated by the digitizer module, corrects for dead time and calculates source activities and their uncertainties. Ampoules with solutions of 113 Sn, 192 Ir and 131 I were measured. Highlights: Implementation of a new measurement system at LMR-CNEA (Argentina). Based on a well-type NaI(Tl) detector. Instruments, methods and uncertainty budget are detailed.